Navigating Legal Boundaries: A Cross-Jurisdictional Comparison of Qanun Jinayat on Non-Muslims in Aceh and Brunei Darussalam - Trini Hastuti, Luthfiyah (DIKTUM: Jurnal Syariah dan Hukum, 2023)
Qanun Jinayah, being a legal framework based on Islamic principles, must prioritize justice and be focused on safeguarding the rights of all citizens, especially the minority non-Muslims in Aceh. The objective of the essay was to conduct a comparative analysis of the criminal laws applicable to non-Muslims in Aceh Province and Brunei Darussalam. This paper's research employs the perspective of doctrinal law, which means that the law is formulated. The author employs legal hermeneutics through the application of grammatical interpretation, which involves analyzing the words in a law in accordance with the principles of language and grammar. The research indicates that application of criminal law is more extensive for non-Muslims in Aceh compared to Brunei. Non-Muslims in Brunei are subject to only two criminal statutes, namely adultery and khalwat. Meanwhile, in Aceh, crimes committed by non-Muslims encompass seven specific offenses, namely khamar (consumption of alcohol), maisir (gambling), khalwat (close proximity between unmarried individuals of opposite genders), ikhtilat (mixing of genders in public spaces), liwath (homosexual acts), musahaqoh (lesbian acts), and qadzaf (false accusation of illicit sexual relations). It is important to note that these seven offenses are not governed by the Criminal Code. However, the procedural legislation of Aceh Qonun Jinayat still requires more regulation to establish a process. The procedural law of Qanun Jinayat does not impose any limitations on the means by which non-Muslims might express their voluntary submission, nor does it specify the stage at which such a statement must be made. For non-Muslims, this criterion becomes a question of legal certainty.